2006
DOI: 10.1080/00103620600710173
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate Adsorption in Soils of North and Northeast Iran

Abstract: Gypsum (CaSO 4 . 2H 2 O) is used in agriculture both as a source of calcium (Ca) and sulphate (SO 4 22 ) and as an amendment to improve soil structure. The effect of gypsum on the adsorption of SO 4 22 in irrigated and nonirrigated soils was examined. Almost all of the indigenous sulphate (SO 4 ) in a range of Golesthan and North Khorasan soils with moderate pH values (.6) was found to be present in the soil solution and, as a consequence, was highly susceptible to leaching. The adsorption of sulphate to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Sulphate adsorption has been attributed to a pH dependent positive charge typical of acidic soils (Scherer, 2009). In neutral to alkaline soils, there was no appreciable adsorption of sulphur noticed (Shahsavani et al, 2006;Cui et al, 2006). The regression analysis between the values of S extracted by Ca chloride (CaCl 2 -S) and Ca phosphate (Ca phos-phate-S) reagents for all the 86 soil samples studied showed that they were highly significantly correlated (R 2 = 0.82, n = 86) (table.…”
Section: Resultsmentioning
confidence: 99%
“…Sulphate adsorption has been attributed to a pH dependent positive charge typical of acidic soils (Scherer, 2009). In neutral to alkaline soils, there was no appreciable adsorption of sulphur noticed (Shahsavani et al, 2006;Cui et al, 2006). The regression analysis between the values of S extracted by Ca chloride (CaCl 2 -S) and Ca phosphate (Ca phos-phate-S) reagents for all the 86 soil samples studied showed that they were highly significantly correlated (R 2 = 0.82, n = 86) (table.…”
Section: Resultsmentioning
confidence: 99%
“…However, when soil pH is in acidic range, soil particles carry some positive charges and, thus, adsorb sulfate. The capability of phosphate to displace sulfate adsorbed on soil-particle surface is stronger than that of chloride; and thus, Ca phosphate extracts significantly greater amounts of S from soils with pH in the acidic range (Ensminger, 1954;Curtin and Syers, 1990;Shahsavani et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…On the suitability of various extractants, it has been stated that Ca phosphate seems to be one of the best extractants, because phosphate ions displace the adsorbed sulfate, especially in acidic-pH soils and Ca 2+ ions flocculate the soil colloids (Fox et al, 1964;Harward and Reisenauer, 1966;Maynard et al, 1987;Schmalz et al, 2001). Among the several factors that influence sulfate sorption-desorption and its extractability by various reagents used for sulfate extraction, soil pH plays a dominant role, and generally the sorption of sulfate is low in soils with pH > 6 (Ensminger, 1954;Curtin and Syers, 1990;Shahsavani et al, 2006;Cui et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos, vários adsorventes têm sido desenvolvidos para a remoção de íons sulfato, tais como: óxidos metálicos [10][11][12][13][14], quitosana [3][4][5][6][7][8][9][10][11][12][13][14][15], óxidos metálicos hidratados [2,16], zeólita [17], goethite [18][19][20][21][22][23] e alguns tipos de solo [24][25]. Dentre estes materiais, os óxidos metálicos são materiais promissores para a remoção desse íon por possuírem elevada afinidade pelos mesmos [19].…”
Section: Introductionunclassified